Rancang Bangun Sistem Informasi Keterlambatan Siswa untuk Meminimalisasi Tingkat Keterlambatan di SMK PGRI Rogojampi - Indana Zulva; Faruk Alfiyan (Jurnal Informatika dan Komputer, 2026)
Educational institutions as learning centers need to be prepared to follow technological developments, especially in the use of information systems that can facilitate work. SMK PGRI Rogojampi faces problems in recording student tardiness which is still done manually, so that the recording process takes a long time, is prone to data loss, and is difficult to search for tardy history. To overcome this, a student tardiness information system is needed that is able to record, store, and manage tardy data in a computerized manner. The system development uses the waterfall method through the stages of needs analysis, system design, implementation and coding, testing, to the maintenance stage. The programming language used is PHP with a MySQL database. Data was collected through interviews and observations to ensure the system meets user needs. This study produces a student tardiness information system to help manage tardy data. The test results show that all features in the system run well and according to their functions. The system is able to handle the process of recording, storing, searching, and reporting tardy data accurately. The main features of the system include login and logout, student and class data input, tardy recording, searching for tardy history, and reporting tardy data. In conclusion, the student tardiness information system developed has succeeded in answering the needs of schools in overcoming manual recording problems. The system not only speeds up work processes and reduces the risk of data loss, but also makes it easier to monitor student discipline.